THE USA AND JAPAN IN WORLD POLITICS - S. V. Volkov (Vestnik MGIMO-Universiteta, 2013)
The complexity and importance of the study of the U.S. – Japan relations in world politics requires continuous improvement of scientific methods. However, works which would analyze the U.S. – Japan relations as a single organism are practically nonexistent. The article analyzes the U.S. – Japan relations as a whole integrative system with a specific structure. The institutionalization of the American- Japanese system, its interaction with world politics are considered especially. The author determines structure of the system, detects leading interactions between its elements, examines the integrity of the American-Japanese system, its levels and hierarchy, dynamics of functioning. The study attempts to prove the author’s methodology which considers bilateral U.S. – Japan institutions as the basis of the American – Japanese system. As part of this methodology the conjugation between the system of bilateral American- Japanese institutions and world politics is analyzed. The dependence of the system on world politics and the dependence of world politics on changes in the U.S. – Japan relations are also revealed. As a result of the study an integral picture of the U.S. – Japan relations is demonstrated. The logic and patterns of their development are determined. It is shown that globalization, changes in balance of power, emergence of a vast number of non-state actors on a world stage changed and continue to change U.S. – Japan relations. What is more, the transformation of the U.S. – Japan relations is the transformation of world politics itself.